2005
DOI: 10.1116/1.2121727
|View full text |Cite
|
Sign up to set email alerts
|

Polymer time constants during low temperature nanoimprint lithography

Abstract: We investigate low temperature nanoimprint into polymers, where adequate pressure choice helps to increase the imprint velocity of larger patterns und thus decreases pattern size effects by reduction of the effective viscosity. In order to make use of shear rate effects, the imprint has to be performed within the viscoelastic plateau region and not in the viscous flow regime of the polymer. Therefore elastic effects play an important role and may lead to shape recovery of the polymer after imprint. We address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…A reduction in temperature has to be compensated by corresponding increases in imprinting pressure and time to obtain satisfactory results. [58] There is a trade-off between the imprinting temperature and the thermal stability, which is illustrated in the following example for polymers with different T g values. Figure 7a shows patterns imprinted in poly(benzyl methacrylate) (molecular weight (M w ) ca.…”
Section: Thermal Plastic Resistsmentioning
confidence: 98%
“…A reduction in temperature has to be compensated by corresponding increases in imprinting pressure and time to obtain satisfactory results. [58] There is a trade-off between the imprinting temperature and the thermal stability, which is illustrated in the following example for polymers with different T g values. Figure 7a shows patterns imprinted in poly(benzyl methacrylate) (molecular weight (M w ) ca.…”
Section: Thermal Plastic Resistsmentioning
confidence: 98%
“…[20,22] Therefore, comparing the time scale for structural relaxations in the bulk polymer to the duration of the imprint process provides some insight into the mold-filling physics. [23] This is done below just for the PS patterns, given the abundant literature on the rheological properties of PS for a range of molecular masses.…”
mentioning
confidence: 99%
“…Moreover, a visco-elastic model should be preferred if the imprint is performed close to the glass temperature, in order to take into account the elastic recovery [4].…”
Section: Application and Discussionmentioning
confidence: 99%
“…Experiments have shown that viscoelasticity model is prone to be the most suitable behavior in general cases [3]. In particular for an imprint temperature close to the glass transition temperature, both experiments [4] and simulations [5] have shown that the elastic effects are predominant. In other cases, shear-thinning can be used [6] as a first step of equations simplification, but this requires to solve non-linear systems.Thus, in a more restricted set of cases, the Newtonian behavior has been used as a cheap and efficient way to predict the polymer flow in micro and nano size cavities.…”
Section: Introductionmentioning
confidence: 99%